2019
DOI: 10.1021/jacs.8b12205
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Hydrophobicity-Induced Immunotoxicity by Sugar Poly(orthoesters)

Abstract: Polymeric nanoparticles (NPs) derived from self-assemblies of amphiphilic polymers have demonstrated great potential in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The hydrophobic part of NPs determines the immune response. Also, cytotoxicity is associated with the degree of hydrophobic substitution of NPs [18]. Therefore, the hydrophobic substitution degree in constructing drug carrier NPs should be carefully controlled, and the important properties and functional changes of NPs caused by different hydrophobic substitutions need investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic part of NPs determines the immune response. Also, cytotoxicity is associated with the degree of hydrophobic substitution of NPs [18]. Therefore, the hydrophobic substitution degree in constructing drug carrier NPs should be carefully controlled, and the important properties and functional changes of NPs caused by different hydrophobic substitutions need investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, hydrophobic materials can be "masked" to prevent removal and reduce intrinsic immune activation by coating them with a hydrophilic material such as polyethylene glycol (PEG), for example. Such a strategy is useful to improve the delivery of vaccines with hydrophobic compounds in the particle core (Maiti et al, 2019). Nevertheless, surface modification of particles additionally modulates their half-life and distribution profile in the body.…”
Section: Charge Hydrophobicity and Other Chemical Propertiesmentioning
confidence: 99%
“…With the advancement in new bioprocesses that use cellulose/lignocellulose as the feedstock; the price is expected to decrease further, and there are hopes that one day this class of polymer may potentially replace certain polymers arising from petroleum. Indeed, there is an increasing number of studies on the synthesis of glucose‐based polymers, as a few of these examples shown in Figure , including sugar polyamide ( IIIa ), sugar polycarbonate ( IIIb ) and sugar poly(orthoester) ( IIIc ) . However, in all of these studies, glucose must be first converted into a polymerizable monomer, often, in a stepwise manner, and requiring chromatographic purification in each step.…”
Section: Figurementioning
confidence: 99%